PJMHS 2021
DOI: 10.53350/pjmhs2115102595
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Steroid-induced Diabetes in COVID-19 patients

Abstract: Background: Since the COVID-19 pandemic has started, glucocorticoids have been proved to be one of the most effective lifesaving treatments for respiratory complications associated with SARS CoV-2. Aim: To review the incidence of steroid induced diabetes and the associated risk factors in COVID-19 patients. Study Design: Retrospective cohort study Place and duration of the study: Bahria International Hospital Lahore from 15th April 2020 to 31st December 2020 Methodology: Two hundred and thirty patients of COV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 12 publications
0
2
0
1
Order By: Relevance
“…For severe COVID-19, glucocorticoids are indicated for lung disease, which may, in turn, increase the risk of diabetes mellitus (12,33,34). For example, in an Indian study, of the 31 individuals who had been treated with steroids while on admission for COVID-19, eleven (35.5%) went on to develop new-onset diabetes three months later (12).…”
Section: Discussionmentioning
confidence: 99%
“…For severe COVID-19, glucocorticoids are indicated for lung disease, which may, in turn, increase the risk of diabetes mellitus (12,33,34). For example, in an Indian study, of the 31 individuals who had been treated with steroids while on admission for COVID-19, eleven (35.5%) went on to develop new-onset diabetes three months later (12).…”
Section: Discussionmentioning
confidence: 99%
“…29 Dos tercios de los pacientes presentaron glicemia en rango de diabetes, lo cual es alto si se compara con lo reportado por Liu et al, quienes hallaron 32,3% de hiperglicemia inducida por corticoides (p=0,003) y 18,6% de diabetes (p=0,002) 30 , o lo reportado por Rana et al, quienes hallaron una incidencia de 15,65% de diabetes. 31 Se ha informado que el uso de corticoides duplica y hasta triplica el riesgo de presentar diabetes mellitus y se asocia a mayor requerimiento de fármacos antidiabéticos. 32 La glucosa al día 20 fue de 14 mg/dl más con dexametasona; si bien es cierto no es significativa respecto a metilprednisolona (p=0,17), tendría su explicación por el tiempo de acción de la dexametasona ya que se ha descrito que, al ser de larga acción, la resolución de la hiperglicemia ocurre a las 24 a 36 horas.…”
Section: Discussionunclassified
“…Of all patients with a history of steroid use, only 33.3% have severe degrees of COVID-19. A higher prevalence was found byRana dkk., (2021), where the majority of a history of steroid use was found in 15.7% of cases [21] Comorbid illnesses are widely recognized as risk factors for COVID-19. This study found that 71.4% had comorbid diseases.…”
Section: International Journal Of Scientific Advances Issn: 2708-7972mentioning
confidence: 99%